Comparative Efficacy of Topical Antifungal and Antiseptic Agents for Otomycosis in Tropical and Subtropical Climates: A Systematic Review and Meta-Analysis - Rachmat Hidayat; Oliva Azalia Putri; Aisyah Andina Rasyid (Sriwijaya Journal of Otorhinolaryngology, 2025)
Background: Otomycosis is a superficial fungal infection of the external auditory canal that is disproportionately prevalent in tropical and subtropical regions, yet the comparative efficacy of topical agents in this climatic and mycological context has not been quantitatively synthesised. Objective: To compare complete-cure rates of topical antifungal and antiseptic agents for otomycosis using comparative studies from tropical and subtropical countries. Methods: Following a registered protocol (PROSPERO CRD420261456091) and PRISMA 2020, we identified comparative studies reporting complete cure or mycological eradication. Ten studies (1,970 ears; eight countries) were included. The pre-specified primary comparison, povidone-iodine versus clotrimazole, was pooled as a risk ratio (RR) using a random-effects model with the Hartung–Knapp–Sidik–Jonkman correction, a 95% prediction interval and a leave-one-out analysis. Risk of bias used RoB 2 and ROBINS-I; certainty used GRADE. Results: The random-effects pooled cure rate across 21 arms was 74.9% (95% CI 66.9–82.2; I² = 93%). For povidone-iodine versus clotrimazole (k = 4), the pooled RR was 0.86 (HKSJ 95% CI 0.53–1.39; prediction interval 0.29–2.58), indicating no significant difference while excluding neither agent's superiority. Between-study heterogeneity (I² = 79%) arose entirely from one non-randomised study; omitting it gave RR 0.95 (0.85–1.06) with I² = 0%. Certainty was low to very low. Conclusion: Topical azoles and low-cost antiseptics such as povidone-iodine achieve broadly similar, moderate cure rates for otomycosis in tropical settings, but the evidence is too imprecise to establish equivalence, and potential ototoxicity means agent choice should remain individualised.